2011
DOI: 10.4304/jltr.2.5.1009-1014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an ESP Textbook for the Students of Sociology

Abstract: Abstract-The present paper is an attempt to describe the process that was undertaken to evaluate the textbook English for the Students of Sociology: Social Science Texts taught at the University of Tehran. The purpose of this research project was to determine the overall pedagogical value and suitability of the book toward this specific language program. To achieve this goal, a questionnaire consisting of 20 items and examining 6 factors (practical concerns, materials in relation to course objective, subject m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…According to Mukundan (2004as cited in Nasiri, 2011 and Ellis (1997as cited in Tok, 2010 there are two types of evaluation: predictive evaluation and retrospective evaluation. As mentioned by Dudley-Evans and St John (1998), Baleghizadeh and Rahimi (2011) divide evaluation into formative and summative types. McDonough and Shaw (2003) regard three classes of evaluations: external, internal, overall.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mukundan (2004as cited in Nasiri, 2011 and Ellis (1997as cited in Tok, 2010 there are two types of evaluation: predictive evaluation and retrospective evaluation. As mentioned by Dudley-Evans and St John (1998), Baleghizadeh and Rahimi (2011) divide evaluation into formative and summative types. McDonough and Shaw (2003) regard three classes of evaluations: external, internal, overall.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It does not consist of a specific kind of language or methodology, nor is it a particular type of teaching material. As the name offers, ESP is designed for a particular group of people in a particular setting and the materials used are relevant to the learners' specialized field of study (Baleghizadeh & Rahimi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of this study indicated that medical ESP textbooks are the right books for the purpose of medical English for Iranian physicians and in harmony with students' requirements and achievements. Baleghizadeh and Rahimi (2011) indicated that the systematic evaluation of textbooks is not often conducted and students' requirements and opinions concerning the materials developed for them are neglected in Iran. Likewise, Eslami-Rasekh (2010) pointed out that ESP textbooks developed for the students of engineering by the Ministry of Higher Education in Iran is not born out of any systematic needs analysis.…”
Section: Related Studymentioning
confidence: 99%
“…The outcomes indicated that most of the subjects had positive attitudes towards both learning English and the English language teacher. Baleghizadeh and Rahimi (2011) indicated that the systematic evaluation of textbooks is not often conducted and students' requirements and opinions concerning the materials developed for them are neglected in Iran. Likewise, Eslami-Rasekh (2010) pointed out that ESP textbooks developed for the students of engineering by the Ministry of Higher Education in Iran is not born out of any systematic needs analysis.…”
Section: Related Studymentioning
confidence: 99%